1996
DOI: 10.1128/jb.178.1.12-18.1996
|View full text |Cite
|
Sign up to set email alerts
|

A global signal transduction system regulates aerobic and anaerobic CO2 fixation in Rhodobacter sphaeroides

Abstract: Complementation of a mutant of Rhodobacter sphaeroides defective in photosynthetic CO 2 reduction led to the identification of a gene which encodes a protein that is related to a class of sensor kinases involved in bacterial signal transduction. The nucleotide sequence and deduced amino acid sequence led to the finding that the gene which complemented the mutant is the regB (prrB) gene, previously isolated from both R. sphaeroides and Rhodobacter capsulatus and shown to regulate the anaerobic expression of str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
81
0

Year Published

1997
1997
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(84 citation statements)
references
References 38 publications
3
81
0
Order By: Relevance
“…sphaeroides. In these bacteria the RegA\RegB system was found to regulate the aerobic and anaerobic expression of genes encoding enzymes of primary and alternative CO # fixation and integrates photosynthesis and nitrogen fixation (Qian & Tabita, 1996 ;Joshi & Tabita, 1996). However, a RegA-like consensus recognition motif (Du et al, 1998) was not found in the sequence of acaP, nor upstream of the coding region, which suggests that a different regulatory system is involved.…”
Section: Localization and Expression Of Camentioning
confidence: 93%
“…sphaeroides. In these bacteria the RegA\RegB system was found to regulate the aerobic and anaerobic expression of genes encoding enzymes of primary and alternative CO # fixation and integrates photosynthesis and nitrogen fixation (Qian & Tabita, 1996 ;Joshi & Tabita, 1996). However, a RegA-like consensus recognition motif (Du et al, 1998) was not found in the sequence of acaP, nor upstream of the coding region, which suggests that a different regulatory system is involved.…”
Section: Localization and Expression Of Camentioning
confidence: 93%
“…In addition to regulating photosynthesis-gene expression, PrrA acts as a global regulator, affecting the expression of genes encoding electron-transport components, genes involved in CO 2 and N 2 fixation, and genes involved in hydrogen oxidation, among others (Elsen et al, 2004;Joshi & Tabita, 1996;Qian & Tabita, 1996). Although the importance of the role played by PrrA in gene regulation is clear, the DNA sequence to which it binds remains poorly defined.…”
Section: Introductionmentioning
confidence: 99%
“…Our results suggest that a similar regulatory mechanism(s) which monitors the ratio of intracellular concentrations of pyruvate and C 4 dicarboxylates may be involved in the control of PC synthesis in R. capsulatus. Recently, RegB-RegA, a global two-component regulatory system, was identified in R. capsulatus and R. sphaeroides and shown to be involved in the control of carbon (CO 2 ) metabolism and photosystem biosynthesis (25,31). However, this regulatory system does not appear to be involved in the regulation of PC synthesis, since a regB mutant showed wild-type levels of PC protein when grown under light anaerobic conditions (47a).…”
Section: Figmentioning
confidence: 99%